Vozes sociais em confronto : sentidos polêmicos construídos discursivamente na produção e recepção de charges - Gonçalves, Tamiris Machado (2015)
Broadcasted in the press, usually via newspaper, the cartoon is a genre whose complexity is set as an interesting object of analysis to observe how the senses are constructed themselves in the discourse. Considering this complexity and based on the Bakhtinian theory, this thesis wants to answer the following question: How is the dialogical construction of senses made, considering the production and reception of the discourse in cartoons that are said to be controversial? The overall objective of this thesis is to analyze how the dialogical construction of the senses happens, considering the enunciative project from the cartoons and the reading of its interlocutors, mainly in those considered to be controversial, thus, cartoons that presented discrepancies between the production and the reception of the senses and that had a repercussion in the media due to a diversity of readings. As specific objectives, we had (a) investigate how the different social voices that go through controversial cartoon engender themselves and reflect and refract senses in the discourse and (b) talk about discourse-response that come out from controversial cartoons. We chose to work with four controversial cartoons and eleven discourse-response from these cartoons, all of them broadcasted on-line between 2011 and 2014, referring to the facts in Brazilian media in between these years. As a theoretical framework, we use the ideas postulated by Mikhail Bakhtin and his Circle, to whom every discourse is dialogic, in other words, the discourse establishes a necessary relation with other discourses, unleashing different senses.Thus, the methodology of analysis is based on the methodological guidance provided in Marxism and Philosophy of Language ([1929] 2009, p. 45). That is to say, the discourse is taken into account from the bond with its socio-historical context, which refers to the need of the analysis to be made from the limits of a particular culture in order to understand the discursive issues engendered in the social spheres from which they emerge. After doing the analysis, we can notice that the discrepancy - between the production and reception of the senses from the controversial cartoons picked - is due to the different valuation by the interlocutors in relation to the project of saying from the cartoon. In addition to that, there seems to be no understanding of what this genre is, which prevents a critical reading. We hope that with the discussions about the constructed senses in the observed discourses, we can contribute with reflections aimed at the teaching of reading and textual production in Portuguese classes, considering the importance of the study of language in use, materialized in different discursive genres.